The impact of Aristotelianism on modern philosophy - Pozzo, Riccardo, 1959- (Washington, D.C. : Catholic University of America Press, 2004)
"In this volume, thirteen distinguished scholars consider the impact of Aristotelianism on modern philosophy. Spanning the last five centuries, the articles examine Aristotelian issues present in the writings of late scholastic, Renaissance, and early modern philosophers, such as: Vernia, Barbaro, Cajetan, Nifo, Piccolomini, Zabarella, Galileo, Campanella, Semery, Leibniz, Rousseau, Kant, Hegel, Nietzsche, Husserl, Heidegger, Wittgenstein, and Gadamer. They trace the impact of the tradtion of Renaissance Aristotelianism, which was first molded by Manuzio's edition of Aristotle's Opera, found its standing in the monumental edition of the Giunti with Averroes' commentary, and reached its blossoming by means of the European diffusion of the works of the Paduan School, first and foremost of Zabarella." "The contributors pay particular attention to the role of the five intellectual virtues set forth by Aristotle in book VI of the Nicomachean Ethics - art, prudence, science, wisdom, and intellect - in modern philosophy."--BOOK JACKET.
Introduction / Riccardo Pozzo -- 1. Aristotle and Some Late Medieval and Renaissance Philosophers / Edward P. Mahoney -- 2. Zabarella, or Aristotelianism as a Rigorous Science / Antonino Poppi -- 3. The Influence of Aristotle on Galileo's Logic and Its Use in His Science / William A. Wallace -- 4. Wrestling with a Wraith: Andre Semery, S. J. (1630-1717) on Aristotle's Goat-Stag and Knowing the Unknowable / John P. Doyle -- 5. Leibniz, Aristotle, and Ethical Knowledge / Christia Mercer -- 6. Speech, Imagination, Origins: Rousseau and the Political Animal / Richard L. Velkley -- 7. Kant on the Five Intellectual Virtues / Riccardo Pozzo -- 8. Hegel's Appropriation of the Aristotelian Intellect / Alfredo Ferrarin -- 9. Tragedy in the Philosophic Age of the Greeks: Aristotle's Reply to Nietzsche / Michael Davis -- 10. The Presence of Aristotelian Nous in Husserl's Philosophy / Richard Cobb-Stevens -- 11. Phronesis or Ontology: Aristotle and Heidegger / Stanley Rosen -- 12. Wittgenstein's Intellectual Virtues / Daniel O. Dahlstrom -- 13. The Reception of Aristotle's Intellectual Virtues in Gadamer and the Hermeneutic Philosophy / Enrico Berti.
Includes bibliographical references (p. 307-328) and index.
Keywords: Aristotle -- Influence; Philosophy, Modern